Evaluating Citizen e-Satisfaction from e-Government Services: A Case of Pakistan - Malik, Babur Hayat; Shuqin, Cai; Shuqin, Cai; Mastoi, Abdul Ghaffar; Mastoi, Abdul Ghaffar; Gul, Noreen; Gul, Noreen; Gul, Hifza; Gul, Hifza (European Scientific Journal, ESJ, 2016)
Citizen satisfaction is a critical and decisive factor for persistent use of e-Government services as it can substantially impact on failure or success of e-Government projects. Main hurdle for e-government planners and practitioners in Pakistan is to find out the key determinants of e-satisfaction of their citizens. This article actually tries to identify the major factors that drive Pakistani citizen’s e-Satisfaction while using Punjab Province Portal (http://www.punjab.gov.pk/) in Pakistan. After extensive relevant literature review we formulated 7 hypotheses and distinguished 7 different determinants namely trust, accessibility, awareness of e-services, quality of e-services, computer anxiety, customer expectations and security/privacy. A sample of survey data from 200 employees in 8 universities in different cities of Punjab Province of Pakistan was gathered to perform data analysis. Several key outcomes based on multiple linear regression and factor analysis were exhibited. These final results would help to understand the degree of satisfaction of Pakistani citizens. E-governmental policy-makers and practitioners both would be benefitted by this analysis and results of these determinants of e-satisfaction. Some recommendations and implications of our findings were also addressed at the end.